Design Procedures for the Use of Composites in Strengthening of Reinforced Concrete Structures State-of-the-Art Report of the RILEM Technical Committee 234-DUC - Pellegrino, Carlo; Sena-Cruz, José.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This book analyses the current knowledge on structural behaviour of RC elements and structures strengthened with composite materials (experimental, analytical and numerical approaches for EBR and NSM), particularly in relation to the above topics, and the comparison of the predictions of the current available codes/recommendations/guidelines with selected experimental results. The book shows possible critical issues (discrepancies, lacunae, relevant parameters, test procedures, etc.) related to current code predictions or to evaluate their reliability, in order to develop more uniform methods and basic rules for design and control of FRP strengthened RC structures. General problems/critical issues are clarified on the basis of the actual experiences, detect discrepancies in existing codes, lacunae in knowledge and, concerning these identified subjects, provide proposals for improvements. The book will help to contribute to promote and consolidate a more qualified and conscious approach towards rehabilitation and strengthening existing RC structures with composites and their possible monitoring.
1. Introduction, by Carlo Pellegrino, José Sena-Cruz -- 2. Design by testing and statistical determination of capacity models, by Giorgio Monti, Antonio Bilotta, Annalisa Napoli, Emidio Nigro, Floriana Petrone, Roberto Realfonzo -- 3. Bond between EBR FRP and concrete, by Claudio Mazzotti, Antonio Bilotta, Christian Carloni, Francesca Ceroni, Tommaso D'Antino, Emidio Nigro, Carlo Pellegrino -- 4. Shear strengthening of RC elements by means of EBR FRP systems, by Giorgio Monti, Tommaso D'Antino, Gian Piero Lignola, Carlo Pellegrino, Floriana Petrone -- 5. Confinement of RC elements by means of EBR FRP systems, by Stavroula Pantazopoulou, Ioannis Balafas, Dionysios Bournas, Maurizio Guadagnini, Tommaso D'Antino, Gian Piero Lignola, Annalisa Napoli, Carlo Pellegrino, Andrea Prota, Roberto Realfonzo, Souzana Tastani -- 6. Special problems -- 6.1. Serviceability limit states, by Francesca Ceroni, Marisa Pecce -- 6.2 Fatigue Behaviour, by Christian Carloni, Thorsten Leusmann, Harald Budelmann.-6.3 Effects of fire and high temperature, by Emidio Nigro, Antonio Bilotta -- 6.4 Long term properties of FRP systems, by Joaquim Barros, Inês Costa -- 6.5 Anchorage systems for external strengthening with FRP, by Francesca Ceroni, Marisa Pecce -- 6.6. Mechanically Fastened Systems, by Gian Piero Lignola, Annalisa Napoli, Roberto Realfonzo -- 7. Prestressed FRP Systems, by Julien Michels, Joaquim Barros, Inês Costa, José Sena Cru2, Christoph Czaderski, Giorgio Giacomin, Renata Kotynia, Janet Lees, Carlo Pellegrino, Edmunds Zile -- 8. NSM Systems, by José Sena-Cruz, Joaquim Barros, Vincenzo Bianco, Antonio Bilotta, Dionysios Bournas, Francesca Ceroni, Glaucia Dalfré, Renata Kotynia, Giorgio Monti, Emilio Nigro, Thanasis Triantafillou -- 9. Fiber reinforced composites with cementitious (inorganic) matrix, by Christian Carloni, Dionysios A. Bournas, Francesca G. Carozzi, Tommaso D'Antino, Giulia Fava, Francesco Focacci, Giorgio Giacomin, Giovanni Mantegazza, Carlo Pellegrino, Carlo Perinelli,Carlo Poggi.
Keywords: Building materials; Mechanics, Applied; Building Materials; Structural Materials; Engineering Mechanics